Scaling Organic Electrochemical Transistors Down to Nanosized Channels. Issue 41 (22nd August 2019) - D'Angelo, Pasquale; Marasso, Simone L.; Verna, Alessio; Ballesio, Alberto; Parmeggiani, Matteo; Sanginario, Alessandro; Tarabella, Giuseppe; Demarchi, Danilo; Pirri, Candido F.; Cocuzza, Matteo; Iannotta, Salvatore
Abstract: The perspective of downscaling organic electrochemical transistors (OECTs) in the nanorange is approached by depositing poly(3, 4‐ethylenedioxythiophene) polystyrene sulfonate (PEDOT:PSS) on electrodes with a nanogap designed and fabricated by electromigration induced break junction (EIBJ) technique. The electrical response of the fabricated devices is obtained by acquiring transfer characteristics in order to clarify the specific main characteristics of OECTs with sub‐micrometer‐sized active channels (nanogap‐OECTs). On the basis of their electrical response to different scan times, the nanogap‐OECT shows a maximum transconductance unaffected upon changing scan times in the time window from 1 s to 100 µs, meaning that fast varying signals can be easily acquired with unchanged amplifying performance. Hence, the scaling down of the channel size to the nanometer scale leads to a geometrical paradigm that minimizes effects on device response due to the cationic diffusion into the polymeric channel. A comprehensive study of these features is carried out by an electrochemical impedance spectroscopy (EIS) study, complemented by a quantitative analysis made by equivalent circuits. The propagation of a redox front into the polymer bulk due to ionic diffusion also known as the "intercalation pseudocapacitance" is identified as a limiting factor for the transduction dynamics. Abstract : A smart approach to the fabrication of sub‐micrometer channel–sized organic electrochemical transistors (nanogap‐OECTs) by an electromigration induced break junction (EIBJ) method is presented. The basic mechanism and key parameters affecting the nanogap‐OECTs characteristics (i.e., response speed and amplification) are analyzed and elucidated through electrical and electrochemical impedance spectroscopy characterization.